Paratextuality of M. Gorky’s Early Journalism (1895-1901) - M. G. Urtmintseva; P. Ye. Yanina (Научный диалог, 2019)
On the material of the first introduced into scientific circulation articles published by M. Gorky in the Nizhny Novgorod press of 1895-1901, the analysis of the functions of pseudonyms as a significant component of the paratext is carried out. As a result of the work, it is established that the pseudonyms chosen and invented by the writer reflect the genre specificity of his feuilletons, essays, bibliographic notes, reviews and replicas, being a kind of marker of the author’s position. It is noted that this kind of paratext as a pseudonym gave the writer’s journalism an additional semantic and emotional impulse, formed the perception of the problems of his feuilletons, which was confirmed by the detailed analysis of the structure and function of the abbreviated form of the pseudonym “I. Khl.” By this example of this pseudonym which is an abbreviation of the nickname “Iegudiil Khlamida,” the authors show that this truncation of the name is due to issues of materials published by Gorky and their presentation. It is proved that pseudonym alludes to the facts, meaning of which is far beyond the interest of the provincial newspaper, and to the role of the author of articles covering not only local problems; for example, in the feuilletons devoted to “the Cretan question,” the author acts as a political observer of international events.